Sequência didática para o ensino e produção de ondas eletromagnéticas - Nascimento, Tiago Viana do (2020)
The teaching of Electromagnetic Waves in High School is present in the National Curriculum Parameters (PCN) as the importance of wave studies for the student's knowledge throughout his life, as various applications from radio transmission to radiation exposure or application in medicine. A problem found in the study of electromagnetic waves is the traditional approach to teaching, where the teacher holds the speech and the student, the listener. This work follows an active learning line, which places the student as the center of the classroom universe in a didactic sequence that addresses the content of electromagnetic waves in which it was applied at the Dom Luciano José Cabral Duarte Center of Excellence. The content to be addressed is part of the curriculum of the third grade of high school, which requires a revision of waves, in which the student will be exposed to a way of remembering the subject in question, such as its nature, type and classification. and the wave phenomena present. For the review, as they are physical concepts, we will adopt the active learning methodology, Instruction by Colleagues (IPC) as well as in the teaching of electromagnetic waves. In addition to the IPC, classes were held with practical experimental activity in the construction of experiments with oscillating circuits responsible for the generation of electromagnetic waves, an FM transmitter radio. The evaluation process takes place with pre-tests in the previous activities and through the conceptual questions applied in the IPC and at the end of the work, post-test, with the application of a final activity of a formative character so that it is an instrument of analysis for the teacher in the which the level of learning achieved by the student group can be verified.